ANALISIS PERBANDINGAN KINERJA LAPORAN KEUANGAN ANTAR PERUSAHAAN DI BIDANG TELEKOMUNIKASI PADA TAHUN 2019-2021 - Ayonda Hayyuani; Neneng Musyrifatul Amelia; Desy Tri Santi Rahmadani; Bella Ari Dwi Puspita K (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The study aims to analyze financial performance comparisons using time series and cross section ratio analysis of the financial statements of the four similar companies in the telecommunications sector during the 2019-2021 period, with telecommunications company objects in Indonesia namely PT Telekomunikasi Indonesia, PT Smartfren Telekom Tbk, PT Bali Towerindo Sentra Tbk, and PT Axiata Tbk. The method used in this study is a qualitative descriptive method, where this method uses research to analyze, describe, and summarize various conditions, situations from which various data are collected. This research produces a comparative analysis of financial performance appraisal using financial ratio analysis, namely analysis of liquidity ratios, activity ratios, solvency ratios, and profitability ratios of PT Smartfren Telekom Tbk., PT Bali Towerindo Indonesia Tbk., PT Axiata Tbk., and PT Telekomunikasi Indonesia. Judging from these three financial ratios, the company can carry out its duties effectively and efficiently because the ratios show an increase in the company's performance in managing the sources of funds it has. However, the company's liquidity ratio cannot be said to have an effective performance because it is still at an abnormal number, namely number 1.